Adverse Perinatal Outcomes Associated with Moderate or Severe Maternal Anaemia Based on Parity in Finland during 2006–10. Issue 5 (17th June 2014) - Räisänen, Sari; Kancherla, Vijaya; Gissler, Mika; Kramer, Michael R.; Heinonen, Seppo
Abstract Background Anaemia during pregnancy is an important public health problem. We investigated whether the association between maternal anaemia during pregnancy and adverse perinatal outcomes differed between nulliparous and multiparous women. Methods A retrospective population‐based cohort study was conducted using data on all singleton births (n = 290 662) recorded in the Finnish Medical Birth Register during 2006–10. Maternal anaemia was defined as a maternal haemoglobin level of <100 g/L). Adverse perinatal outcomes that were examined included preterm delivery (<37 weeks), small‐for‐gestational age (SGA, <2 standard deviation), admission to neonatal intensive care, stillbirth, early neonatal death, and major congenital anomalies. An association between anaemia and adverse outcomes was assessed by logistic regression analysis. Results The prevalence of anaemia during pregnancy was 2.5% among nulliparous women and 2.3% among multiparous women. Among nulliparous women, anaemia was not associated with adverse perinatal outcomes. Among multiparous women, anaemia was associated with preterm delivery (adjusted odds ratio [aOR] 1.32, [95% CI 1.14, 1.53]), SGA (aOR 1.27, [95% CI 1.04, 1.55]), and admission to neonatal intensive care (aOR 1.23, [95% CI 1.10, 1.38]); there was a trend towards increased odds of major congenital anomalies (aOR 1.15, [95% CI 0.99, 1.34]). Conclusions These data underscore that maternal anaemia is associated with several adverse perinatal outcomes. This association was, however, confined to multiparous women. Future research should explore in detail the timing of anaemia in these associations.